Accountability in the post-Lisbon European Union - Brandsma, Gijs Jan; Mastenbroek, Ellen; Heidbreder, Eva (2016)
This special issue takes stock of recent post-Lisbon additions to the European Unions accountability toolkit. It provides indications that older decision-making tools tend to be more accountable than newer ones, and that, in some areas, decision-making is shifting towards less accountable arenas. This introductory article reviews the debate on the gradual evolution of the European Union's accountability system and introduces key aspects of the post-Lisbon era that can be expected to affect accountability in the European Union, and that have been overlooked by the literature thus far: delegated acts, economic governance and regulatory evaluations. The contributions to this special issue address each of these domains in detail and highlight the degree to which accountability has been enhanced. A final contribution shows how these arrangements fit into the wider landscape of already-existing European Union accountabilities and how this landscape has developed over time.
Keywords: Accountability; European Union